OLAHRAGA, MEDIA, DAN TEKNOLOGI - Yan Indra Siregar; Putra Arima; Hemaliani Jouys Panjaitan; Hirspel Dikson Samuel Ritonga; Ahmad Arivaldi; Aulia Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of media and technology has had a significant impact on the world of sports. Media is the primary means of disseminating sports information to the public, while technology helps improve the quality of matches, athlete performance, and the spectator experience. This article aims to discuss the relationship between sports, media, and technology in modern life. The research method used is a literature review, reviewing various scientific sources related to the sociology of sport and the development of sports technology. The results of the discussion indicate that media and technology play a significant role in the development of sports, including in communication, education, entertainment, and performance. However, these developments also pose challenges such as the commercialization of sports and dependence on technology.